Fokus pengguna sebagai good service care di kantor perpustakaan dan arsip daerah kabupaten gunung kidul - Hirma Susilawati (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
The purpose of writing this article is to find out whether Gunadarma University's Library is applying the user focus, then how to apply the user focus in the library because it can be seen that the information needs of each person is varied and more complex. It indirectly requires libraries to develop and pay attention to these things so that it can innovate and follow the development of information that exist in today's society. The theory used is custumer oriented because considering the needs of each individual is very complex and different so that custumer oriented can be said accordingly. The type of research used is descriptive analysis and the result shows good service care done by party such as free internet service and hot spot, integrated art room service (modern musical instrument, gamelan, ape, cd / dvd, play station, etc.) craft services, home theater, edu galleries, cultural collections, comic corners, rock, rock and soil research services in Gunungkidul district, storytelling services, dance studio and painting studio, library and archive consultancy services, visit library, and gift giving smart. Besides also utilizing the internet media and cooperation with various parties to develop the library became better.Keywords: library, good service, user